Is the foodservice industry perceived as being palatable by those looking to enter it?. Issue 4 (4th July 2022) - Holmes, Mark Robert; McAdams, Bruce; Gibbs, Chris; D'Angelo, Alexia
ABSTRACT: This research looks to examine attractors and detractors for students looking to enter the hospitality and culinary industries, their perceptions of work/life balance, and their schedule preferences. To accomplish this, surveys were undertaken at 2 universities and 6 colleges located in Ontario, Canada. This study found that the long hours, mid shifts, and work-life balance deter students in culinary and hospitality programs from wanting to enter the industry and that there is a preference for four-day workweeks. The paper concludes by discussing the preferences of tomorrow's workforce, proposing that the foodservice industry should look to offer schedules that will improve employee wellbeing and retention.